Pemberantasan Pungutan Liar Sebagai Tindak Pidana Korupsi Pada Dinas Perhubungan Kabupaten Badung - Ni Komang Laksmi Ari Widya Pramesti; Simon Nahak; I Wayan Arthanaya (Jurnal Analogi Hukum, 2021)
Corruption is an extraordinary crime (extraordinary crime) of the government and when law enforcement in its handling must have a strong determination and power. One of the criminal acts of corruption is illegal levies, acts of retribution which are a social phenomenon that existed before the Indonesian State became independent. Along with the development of technology and information on developments in the era of globalization has a huge influence on human life and civilization. Stimulates the human mind, giving rise to various problems that have positive and negative effects. These problems can be examined as follows: 1) what is the role of the community in eradicating Illegal Levies as a Corruption Crime? 2) How is Law Enforcement of Illegal Levies as a Corruption Crime at the Badung Regency Transportation Service? This presentation uses Empirical research methods, and requires primary data as the main data in addition to secondary data. The role of the community in efforts to prevent and eradicate Corruption Crime is contained in article 41 (1) Law No. 20 of 2001 changes to Law No. 31 of 1999 The Corruption Act which we know more about the Law on the Eradication of Corruption Crime. Prevention and eradication of Corruption Crimes in the form of seeking, obtaining, providing data or information on Corruption Crimes and the right to submit suggestions and opinions responsibly for the prevention and eradication of Corruption Crimes. Wild levies are actions that are intentionally carried out to enrich themselves, groups, or corporations.